Dental Monitoring Application of Simogi to Change Parental Behavior for Maintaining Children Dental Health - Salikun Salikun; Supriyana Supriyana; Suwarsono Suwarsono (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2023)
Children's oral and dental health needs to be maintained from an early age in order to sustain the integrity of their teeth. A new dental health care monitoring named SIMOGI (Dental Health Monitoring System) application is proposed. This application is used by parents and it’s integrated with dental therapist’s account. The application has features of dental health care checklist and dental danger sign. The aim of this study is to analyze changes in parental behavior towards the maintenance of children's oral health with the implementation of SIMOGI. This research is an experimental study with pretest and posttest design with control group design. The total sample used is 20 parents of elementary school in grade 3. A behavioral questionnaire on dental and oral health maintenance on knowledge, attitudes and actions were done to measure the effect changes. The category is grouped into bad, fair and good. This experiment ran for 21 days. The analytical test used is univariate analysis, bivariate analysis using the Wilcoxon test. The results show that in knowledge, there is no effect on control (p-value 1.000) and intervention group (p-value 0.785). There is effect on intervention group’s attitude (p-value 0.018) and no effect on control group (p-value 0.317). There is effect both in intervention (p-value 0.024) and control group (p-value 0.102). There is an effect of using the SIMOGI application on changes in parents' attitudes and actions in maintaining children's dental health. Knowledge of the parents is already in the good category.